EMPOWERMENT OF PKK COOPERATIVE JULI COT MEURAK TO INCREASE COMMUNITY INCOME IN ORDER TO SUPPORT SDGS AND ACCELERATE THE ERADICATION OF EXTREME POVERTY (P2KE) - Mai Simahatie; Cut Fadhilah; Imam Malik; Ashraf Mauliddin; Nuratul Syiva; Rizaki Akbar (RADJA PUBLIKA, 2024)
One of the strategies used to empower women is to empower